2013
DOI: 10.1080/15374416.2012.759117
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Girls' ADHD Symptoms and Young Adult Driving: The Role of Perceived Deviant Peer Affiliation

Abstract: Objective Our goal was to examine the role of adolescent perceived deviant peer affiliation in mediating or moderating the association between adolescent attention-deficit/hyperactivity disorder (ADHD) symptoms and young adult driving risk in females with and without ADHD. Method The overall sample included 228 ethnically and socioeconomically diverse girls with or without a diagnosis of ADHD in childhood (Wave 1; 6–12 years) followed through adolescence (Wave 2; 11–18 years) and into young adulthood (Wave 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Kingery and colleagues (2015) found that adolescents with ADHD demonstrated increased inattention in simulated distraction tasks, such as texting or phone calls, with a larger percent of their time with their eyes diverted from the roadway. Additionally, in a sample of adolescent girls, inattention was associated with their young adult driving crashes relationships (Cardoos, Loya, & Hinshaw, 2013). Our findings demonstrate that symptom severity of inattention—and not just ADHD diagnostic status—is associated with risky driving.…”
Section: Discussionmentioning
confidence: 99%
“…Kingery and colleagues (2015) found that adolescents with ADHD demonstrated increased inattention in simulated distraction tasks, such as texting or phone calls, with a larger percent of their time with their eyes diverted from the roadway. Additionally, in a sample of adolescent girls, inattention was associated with their young adult driving crashes relationships (Cardoos, Loya, & Hinshaw, 2013). Our findings demonstrate that symptom severity of inattention—and not just ADHD diagnostic status—is associated with risky driving.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample included only female adolescents and is not necessarily generalizable to male adolescents. This design feature of this study could be considered strength since elevations in ADHD symptoms in females are associated with negative functional outcomes (e.g., Cardoos, Loya, & Hinshaw, ). Future studies should consider gender as a moderator of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of teen drivers without ADHD have consistently found that parents and peers play significant roles in their driving outcomes. The same is true for teen drivers with ADHD (Cardoos, Loya, & Hinshaw, 2013). For example, teenagers who report better relationships with their parents engage in less risky driving.…”
Section: Peers Matter But So Do Parents!mentioning
confidence: 75%